Efeito do ácido alfa-lipóico sobre biomarcadores de estresse oxidativo, inflamação e fatores de risco cardiovascular em hipertensos - Portela, Alyne da Silva (2013)
Alpha-lipoic acid (ALA) is a potent antioxidant with favourable anti-inflammatory, metabolic and endothelial effects, and has been widely investigated due to its potential against cardiovascular risk factors. This study aimed to evaluate the effect of oral ALA supplementation on oxidative stress biomarkers, inflammation and cardiovascular risk factors in patients with hypertension. This is a double-blind placebo-controlled randomized clinical trial, where the intervention was evaluated prospectively comparing results in both groups. The sample consisted of 64 hypertensive patients who were randomly distributed into ALA group (n = 32), receiving 600 mg / day ALA for twelve weeks and control group (n = 32), receiving placebo for the same period. The following parameters were evaluated before and after intervention: lipid peroxidation, content of reduced glutathione (GSH), enzymatic activities of glutathione peroxidase (GPx) and superoxide dismustase, ultrasensitive C-reactive protein (hs-CRP), triglycerides, total cholesterol and fractions, fasting glucose and anthropometric indicators. There was a statistically significant reduction (p <0.05) in serum concentrations of total cholesterol, very low density lipoprotein (VLDL), high density lipoprotein (HDL), triglycerides and blood glucose. There was a reduction in body weight and waist, abdominal and hip circumferences in the group that received ALA. In addition, there was a statistically significant increase (p <0.05) in the contents of reduced glutathione (GSH) and glutathione peroxidase (GPx) in the group receiving ALA. Oral administration of ALA appears to be a valuable adjuvant therapy, which may contribute to decrease the damage caused by oxidative stress and other risk factors associated with the atherosclerotic process